RANCANG BANGUN APLIKASI PENGUKURAN TINGGI BADAN, BERAT BADAN, SUHU TUBUH, DAN TEKANAN DARAH BERBASIS MIKTROKONTROLER ATMEGA16 - Dewi, Ratih Kusuma; Subari, Arkhan (Vocational School Diponegoro University, 2012)
Ratih Kusuma Dewi, Arkhan Subari, in paper design and application of measurement stature , body weight , body temperature , and pressure based miktrokontroler atmega16 explain that now almost all uses of automation , both in the world of health . Equipment needed is the automation of the measurement tool capable of measuring several variables simply using a tool . The tool consists of ultrasonic sensors as a means of height measurement , the sensor strain guage as a means of weight measurement , LM35 temperature sensor as a means mengkuran body temperature , as well as a combination of MPX5100DP pressure sensors , motor driver , relay driver , as well as a mini compressor pressure gauge blood . The method used in the manufacture and testing of the tool by comparing the output of this tool with measuring devices in the market . The measurement results will be issued in the form of LCD , Voice Processor , and Database . Height measurement tool using these tools has a percentage error of 1.52 % , while for 2.314 % of body weight , body temperature by 1.62% , to pressure systole of 1.41 % , and for the pressure dystole of 0.858 % . Keywords : Ultrasonic Sensor, Strain Guage Sensor, Sensor LM35, MPX 5100DP, Microcontroller ATMega16.